An Important Finding of Systemic Aspergillosis: Skin Involvement and Amphotericin B Resistance in an Adolescent - Aslinur Ozkaya-Parlakay; Buse Ozer-Bekmez; Ates Kara; Baris Kuskonmaz; Zuhal Akcoren; Sevtap Arikan-Dagli; Berna Oguz (Elsevier, 2016)
Invasive aspergillosis is a life-threatening infectious complication in immunocompromised patients, especially with malignancy, and in some cases, it causes extensive tissue destruction and subsequent systemic illness, leading to multiorgan failure and death. Skin involvement and amphotericin B resistance are very rare findings of aspergillosis. Herein, we report the case of a primary hemophagocytic syndrome patient who developed subcutaneous nodules in the 3rd month of bone marrow transplantation from which Aspergillus fumigatus was cultivated despite the fact that she was under antifungal therapy. In immunocompromised patients with prolonged fever, atypical presentations of invasive mycosis should be kept in mind, and early appropriate therapy should be initiated promptly to decrease morbidity and mortality.